Toolshed. (Downbeat, 2010)
The article evaluates several sound recording equipment including the Strum Electric GS-1 guitar track plug-in from Applied Acoustics Systems DVM Inc., 4K Buss Compressor from the Universal Audio Inc., and the H-Comp Hybrid Compressor from Waves Audio Ltd.